Recognizing Bell's Palsy: What the Family Physician Should Know - Dale, C. C. H. (1973)
This article discusses the etiology, diagnosis and management of Bell's Palsy, stressing the beneficial results of steroid therapy with large doses of Prednisalone. Differential diagnosis, investigative procedures, and indications for surgery are outlined.